Aproveitamento de energia vertida turbinável para produção de hidrogênio e geração distribuída - Carnieletto, Renata (2011)
In many hydroelectric power plants, while the water inflows are greater than demand, part of this water that could be used to generate energy is spilled by the dam gates and literally wasted. This dissertation discusses the use of this wasted hydroelectric potential for hydrogen (H2) generation through water electrolysis. The usage of this hydrogen can happen not only in vehicle engines or industrial applications, but in energy generation through fuel cells and behaving as an energy vector. The H2 production by electrolysis requires an energy source for its processing. This dissertation aims at to mitigate this issue by the use of the secondary energy. Besides the H2 generation aspects, it is presented the complete mathematic model of alkaline electrolyzers. With respect to the wasted hydroelectric potential approach it must be taken into account that alternative sources of energy are settled onto three bases: the energy source itself, the distribution grid and the interconnection energy source-to-grid (or source-to-load). Looking at this fact, the source connection and disconnection from the grid is a challenge for systems engineering. For this dissertation the simulation of Voltage Source Inverters (VSI) was selected to represent the islanded and grid tied conditions. For that, it is proposed an anti-islanding algorithm used to protect the system against faults that may occur in the grid. A reconnection algorithm is also included to obtain the synchronism of the alternative source with the electric grid. To control these inverters, two control techniques are presented along this text: DQ-frame and the proportional and resonant (P+Resonant) control. These control techniques are simulated to evaluate the application efficiency of such controllers. Additionally a smart control in perspectives of the smart grid was also developed and it is proposed in this dissertation. A smart grid integrated to the distribution system allows aggregation of efficient actions of all agents related to electricity services and so strategically making available the electricity goods and services. In this context, based on real-time spot pricing of the electricity obtained from the utility using an advanced metering device, the inverter control algorithm determines the optimal operating mode. This algorithm enables the inverter to: a) schedule local loads; b) determine either to local storage or selling of energy to the grid. Finally, it is shown that on-line fault detection in the system can also make possible a fast restoration of most contingence situations.